Evaluating preventive measures for the zoonotic transmission of swine influenza A variant at agricultural fairs in the United States: a mathematical modeling study - Pittman Ratterree, Dana C.; Dass, Sapna Chitlapilly; Ndeffo-Mbah, Martial L. (Frontiers in Veterinary Science, 2025)
IntroductionSwine exhibitions at agricultural fairs serve as unique environments where humans and pigs interact, and swine influenza A can spill over. As agricultural fairs present a substantial risk for zoonotic influenza outbreaks and potential pandemics, it is paramount to identify efficient preventive measures for mitigating the risk of variant influenza A transmission from pigs to humans at swine exhibitions.MethodsWe developed a mathematical model of swine influenza A variant transmission at agricultural fairs. We fitted the model to empirical data of a 2011 zoonotic outbreak at a Pennsylvania agricultural fair. We used the fitted model to simulate and evaluate the impact of various control strategies, including preventive measures such as shortening the exhibition duration, enhanced biosecurity, pre-fair testing of pigs, and quarantine of sick animals.ResultsThe impact of control strategies was shown to vary substantially between preventive measures. Shortening the length of the exhibition to 3 days generated the lowest prevalence of disease in pigs and humans. Increased biosecurity measures reduced the risk and size of swine influenza outbreaks among pigs and humans during the exhibition period. Due to the majority of pigs experiencing asymptomatic infections, case identification and quarantining of sick pigs did not significantly reduce the infection prevalence.ConclusionShortening the duration of swine exhibitions combined with enhanced biosecurity measures was shown to be the most effective method for preventing zoonotic transmission of swine influenza during agricultural fairs in the US. The study provides additional evidence on the potential benefits of shortened swine exhibitions.